2021
DOI: 10.1002/ctm2.482
|View full text |Cite
|
Sign up to set email alerts
|

Serum extracellular vesicles containing MIAT induces atrial fibrosis, inflammation and oxidative stress to promote atrial remodeling and atrial fibrillation via blockade of miR‐485‐5p‐mediated CXCL10 inhibition

Abstract: Background Atrial fibrillation (AF), a supraventricular arrhythmia that impairs cardiac function, is a main source of morbidity and mortality. Serum‐derived extracellular vesicles (EVs) have been identified to carry potential biomarker or target for the diagnosis and treatment of AF. We intended to dissect out the role of lncRNA MIAT enriched in serum‐derived EVs in AF. Methods MIAT expression was quantified in EVs isolated from serum samples of AF patients. Mouse and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…A study has shown that CXCL10 can predict the prognosis of patients with advanced serous OV [39]. Increased CXCL10 expression promotes atrial fibrosis, inflammation, and oxidative stress [40]. A study has shown that FDCSP promotes the invasion and migration of OV cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that CXCL10 can predict the prognosis of patients with advanced serous OV [39]. Increased CXCL10 expression promotes atrial fibrosis, inflammation, and oxidative stress [40]. A study has shown that FDCSP promotes the invasion and migration of OV cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that lncRNAs play pivotal roles in cardiovascular disease, including organ injury and fibrosis, development by functioning as ceRNAs to bind with miRNAs ( 44 , 45 ). For example, serum extracellular vesicles carrying lncRNA MIAT induce atrial injury, inflammation, and fibrosis to promote atrial remodeling and atrial fibrillation via sponging to miR-485-5p ( 46 ). The upregulation of lncRNA DCRF increases myocardial fibrosis, injury, and the acceleration of cardiomyocyte autophagy levels by acting as a ceRNA to sponge with miR-551b-5p ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the research on the effect of mir-485-5p on the morphology and function of the cardiovascular system shows contradictory conclusions, which may be caused by the selection of different myocardial fibrosis models (24). Mir-485-5p promoted cardiac fibrosis in the isoproterenol-induced model, while mir-485-5p showed cardioprotection in the acute myocardial infarction model (25). Therefore, the role of mir-485-5p in cardiac fibrosis deserves further study.…”
Section: Mir-485-5p Inhibits the Activation Of Cardiac Fibroblastsmentioning
confidence: 99%